Examination of Elemental Composition of Herbal Medicinal Raw Materials of Voronezh Region - N. A. Dyakova (Разработка и регистрация лекарственных средств)
Introduction. The available information on the elemental composition of medicinal plant raw materials of the Voronezh region showed that studies are carried out mainly on several elements, which does not allow determining the complete mineral complex of medicinal plants and describing the specifics of the accumulation of individual elements in them.Aim. The purpose of the study is to study the macro- and microelement composition of medicinal plant raw materials of the Voronezh region on the example of a protected area.Materials and methods. Pharmacopoeic types of medicinal vegetal raw materials were used as subjects of investigation: nettle leaves dioecious (Urtica dioica L.), plantain leaves large (Plantago major L.), common pajma flowers (Tanacetum vulgare L.), heart-shaped linden flowers (Tilia cordata Mill.), herb of five-lobed dumplings (Leonurus quinquelobatus Gilib.), grass of bitter wormwood (Artemisia absinthium L.), common millennium grass (Achillea millefolium L.), bird mountain grass (Polygonum aviculare L.), roots of the common bladder (Arctium lappa L.), roots of the dandelion drug (Taraxacum officinale F.H. Wigg). Raw material harvesting was carried out in accordance with pharmacopoeic rules in natural thickets in the Voronezh State Natural Biosphere Reserve named after V. M. Peskov in the Ramonsky district. The microelement composition of the samples was studied mass-spectroscopically on an ELAN DRC device (PerkinElmer Instruments, USA) after acid-microwave decomposition.Results and discussion. In each plant sample, 59 elements were quantified. The content of the total elemental complex in the studied types of LRs varies from 1.91 to 7.68 % in terms of dry raw materials. The studied raw materials accumulate macroelements to the greatest extent (more than 84 %). Essential trace elements accumulate most in dioecious nettle leaves (more than 9 mg/g). Of the essential trace elements, silicon and iron accumulate most of all the studied raw materials. Content of regulated toxic trace elements does not exceed requirements of pharmacopoeia.Conclusion. The results of the study showed a complex macro- and microelement composition of the studied medicinal vegetal raw materials, which can be used in the medical and pharmaceutical practice of creating phytopreparations and biologically active additives for correcting physiological norms of the content of elements in the human body. The most quantitatively rich elemental composition is noted for the grass of five-lobed dumplings, nettle leaves of dioecious and large plantain (more than 50 mg/g).